Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pelanggan Go-Jek (Studi Pada Mahasiswa Administrasi Niaga Politeknik Negeri Jakarta) - Soraya Khairiyah; Titik Purwinarti; wahyudi Utomo (Administratif Profesional, 2020)
SORAYA KHAIRIYAH. The influence of Service Quality to Customer Loyality of Go-Jek. Department of Business Administration, Politeknik Negeri Jakarta, 2017. The purpose of this research is to analyze the influence of service quality against the customer loyality. The brand image variables has five indicators. 1)tangible, 2)reliability, 3)responsiveness, 4)assurance, 5)empathy. While the customer loyality variables having six indicators, 1)the repurchasing, 2)habit of consuming the brand , 3)always liked the brand, 4)keep choosing the brand, 5)convinced that the brand is the best, and 6)recommend the brand to others. The research of quantitative approaches to wear by using purposive sampling technique, namely the determination of the sample with a particular consideration. The number of samples used in this research about 81 respondents. The results of this research showed that variables of service quality has positive influence on the customer loyality of Go-Jek in Business Administration student, Politeknik Negeri Jakarta. Because in this study, the 35,6% of the customer loyality of Go-Jek can be influenced by service quality. While the rest of 64,4% is explained by other factors outside the model analyzed.